Islamic Republic of Afghanistan : Fourth Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on the Fourth Review Under the Staff-Monitored Program (SMP) for Afghanistan. Under the SMP, Afghanistan continued to make progress in improving macroeconomic management, strengthening its capacity to formulate policy, and creating conditions for sustainable economic growth. All indicative quantitative indicators and structural benchmarks for the fourth review were observed, except for the external debt survey, owing to the lack of cooperation of some creditors. Despite unfavorable weather, real GDP continued to increase at a steady pace, estimated at 7.5 percent in 2004/05.